Influenced Factors on Teacher Accountability to Enhance Student Leaning Outcomes at Lower Secondary School in Cambodia - Sauth Syna; Mam Socheath (Srawung: Journal of Social Sciences and Humanities, 2026)
Teacher accountability is a critical factor in improving student learning outcomes, yet its influencing factors remain underexplored in Cambodian lower secondary schools. This study addresses the gap by investigating both internal and external factors, such as self-motivation, self-commitment, professional development, peer collaboration, school leadership, policy and regulation, feedback, teaching efficacy, social fund and community engagement that shape teacher accountability. The purpose of the research was to examine the extent to which these factors contribute to teachers’ responsibility in enhancing student achievement. A qualitative approach was employed from document study, focus group discussions and semi-structured interviews with 77 participants, including school management teams, teachers, parents, and students from two provinces. Data were thematically analyzed using NVivo software. Findings revealed that self-motivation and self-commitment strongly drive teacher accountability, fostering persistence, innovation, and professional responsibility. External factors, particularly professional development, peer collaboration, supportive leadership, and active community involvement, further reinforce accountability by providing resources, guidance, and shared responsibility for learning. The study concludes that fostering both intrinsic motivation and supportive external environments is essential for sustaining teacher accountability and improving student learning outcomes in Cambodian lower secondary schools.